2014
DOI: 10.1200/jco.2013.53.6037
|View full text |Cite
|
Sign up to set email alerts
|

Can Patient Navigation Improve Receipt of Recommended Breast Cancer Care? Evidence From the National Patient Navigation Research Program

Abstract: Purpose Poor and underserved women face barriers in receiving timely and appropriate breast cancer care. Patient navigators help individuals overcome these barriers, but little is known about whether patient navigation improves quality of care. The purpose of this study is to examine whether navigated women with breast cancer are more likely to receive recommended standard breast cancer care. Patients and Methods Women with breast cancer who participated in the national Patient Navigation Research Program were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 38 publications
(13 reference statements)
1
90
0
Order By: Relevance
“…The Patient Navigation Research Program, the largest study to date of patient navigation located at nine sites across the US showed benefits in cancer care, with a greater proportion of patients initiating cancer care in a timely fashion [20], with the benefits focused on those who had not initiated cancer care within 90 days of diagnosis. This study documented a greater adherence to guideline recommended care among the navigation arm of the study [21].…”
Section: Patient Navigation In Cancer Carementioning
confidence: 74%
“…The Patient Navigation Research Program, the largest study to date of patient navigation located at nine sites across the US showed benefits in cancer care, with a greater proportion of patients initiating cancer care in a timely fashion [20], with the benefits focused on those who had not initiated cancer care within 90 days of diagnosis. This study documented a greater adherence to guideline recommended care among the navigation arm of the study [21].…”
Section: Patient Navigation In Cancer Carementioning
confidence: 74%
“…Navigators should ideally be breast nurses but lay-health professionals with strong communication skills and sufficient experience may also address complex care and mixed cultural settings 26 . Studies have shown that incorporating navigators in health clinics improves patients' sense of empowerment and increases the uptake of standard therapies [26][27][28] .…”
Section: Methodsologymentioning
confidence: 99%
“…Ko et al [47] examined whether patient navigation improved receipt of recommended breast cancer care. In this study, women with breast cancer who participated in the national Patient Navigation Research Program were examined to determine whether the care they received included: initiation of antiestrogen therapy in patients with HR-positive breast cancer; initiation of postlumpectomy radiation therapy; and initiation of chemotherapy in women less than 70-year-old with TN tumors greater than 1 cm.…”
Section: Overview Of Treatment Appropriateness and Navigation Researchmentioning
confidence: 99%
“…Treatment appropriateness was addressed by one study, in terms of patient treatment navigation (Table 5) [47]. Ko et al [47] examined whether patient navigation improved receipt of recommended breast cancer care.…”
Section: Overview Of Treatment Appropriateness and Navigation Researchmentioning
confidence: 99%